2017
DOI: 10.14295/bds.2017.v20i2.1408
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Subcutaneous Tissue Response to Microorganisms Associated with the Extract of Araçá (Psidium cattleianum): An Edemogenic and Microscopic Analysis

Abstract: <p><strong>Objective:</strong> To evaluate <em>in vivo </em>tissue reaction to the extract of araçá (<em>Psidium cattleianum</em>) associated with inactivated microorganisms. <strong>Material and Methods:</strong> A 0.1 mL suspension was used containing Porphyromonas gingivalis, Prevotella intermedia, <em>Fusobacterium nucleatum, Enterococcus faecalis, Peptostreptococcus micros</em>, and <em>Porphyromonas endodontalis,</em> which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The effect of natural compounds, such as plant extracts, on the oral biofilm and their impact on microbial ecolog y has been widely stud ied. 9,10,11,12,20,23,24,25,26 The null hypothesis was rejected, once the extracts induced a mild inflammatory reaction after 30 days, similar to the control group. The biocompatibility of the aroeira extracts containing inactivated microorganisms were chosen, because the previously reported antimicrobial effect.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of natural compounds, such as plant extracts, on the oral biofilm and their impact on microbial ecolog y has been widely stud ied. 9,10,11,12,20,23,24,25,26 The null hypothesis was rejected, once the extracts induced a mild inflammatory reaction after 30 days, similar to the control group. The biocompatibility of the aroeira extracts containing inactivated microorganisms were chosen, because the previously reported antimicrobial effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that associations of facultative anaerobes and anaerobes are capable of inducing inflammation. 2,27 The methodology of inflammatory tissue response assessment with plant extract containing inactivated bacteria was recently reported by Machado et al 20 Some anaerobic species lost their viability within the connective tissue of mice, even before the first trial period. 27 For this reason, we opted to use inactivated microorganisms to avoid obtaining false positive results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations